THE EFFECT OF BRAINWRITING STRATEGY IN WRITING SKILL RECOUNT TEXT AT ELEVENTH GRADE STUDENT OF SMA SWASTA KAMPUS NOMMENSEN PEMATANGSIANTAR - Julita Lumban Raja; David Togi Hutahaean; Siska Anggita Situmeang (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
The purpose of this study was to determine whether the Brainwriting Strategy has a significant effect on the recount text writing skills of grade XI students of SMA Swasta Kampus Nommensen Pematangsiantar. This study used a two-group design (quasi-experimental) by providing Brainwriting Strategy treatment to the experimental group and without the strategy to the control group. Data were collected through pre-test and post-test writing and analyzed using a t-test. The results of the analysis showed a very significant increase in the experimental group with an average post-test of 85.2, much higher than the control group which only reached 74.28. The t-test value of 6.482 with Sig. (2-tailed) 0.000 (p<0.01) validates that there is a significant effect of the Brainwriting Strategy in improving students' recount text writing skills. This indicates that the alternative hypothesis (H0) was accepted and the null hypothesis (H1) was rejected. This strategy has proven to be very effective in encouraging students to generate ideas. and improve the quality of their writing.